The Need for Access to Judicial Information and Its Impact on Society - Mohammadi, Fathullah (Integrated Journal for Research in Arts and Humanities, 2025)
Access to judicial information in Afghanistan is highly limited due to the absence of a dedicated law addressing this issue. Thus, I decided to conduct research on this topic, titled "The Need for Access to Judicial Information and Its Impact on Society", to shed light on its ambiguous aspects. The significance of this topic is evident, as individuals encounter numerous challenges in daily life, some of which are personal, while others are societal. Among societal challenges, certain issues cannot be resolved without a judicial ruling. For instance, when disputes arise between individuals, where each party claims their right to the disputed matter, the judge must determine who is entitled and who is not. However, some individuals do not accept the judicial ruling, prompting the government to intervene and enforce the decision using its authority to resolve the issue. To ensure the validity of claims and for judicial decisions to be transparent, just, and trustworthy in the light of Sharia law, it is essential that people are informed about these proceedings. This information and awareness have significant positive effects on society, steering it toward constructive change. These benefits have been thoroughly explored in the thesis's discussions and text. Based on this foundation, this research delves into the definition, types, historical background, principles, and boundaries of judicial information; the methods for accessing such information; its necessity, limitations, and benefits. In the absence of judicial information, trust in the fairness and legitimacy of judicial decisions cannot be established. The right to access information is enshrined in both national and international legal frameworks. Methods of accessing judicial information include attending court sessions, taking notes during sessions, recording audio, filming, and interviewing judges. I conducted this research using explanatory, inductive, and library-based methodologies. In collecting topics, I first prioritized utilizing credible sources, and where such sources were unavailable, I referred to alternative references. At the conclusion of this research, I examined the definition, types, history, methods of access, necessity, limitations, and benefits of judicial information. Additionally, the presence of judicial information in national and international documents was clarified, as well as its impact on Afghan society.